Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1161/01.cir.103.7.993
|View full text |Cite
|
Sign up to set email alerts
|

Statins Alter Smooth Muscle Cell Accumulation and Collagen Content in Established Atheroma of Watanabe Heritable Hyperlipidemic Rabbits

Abstract: This study showed that statins can reduce MMP expression in atheroma and that cell-permeant statins can decrease SMC number and collagen gene expression in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
227
2
13

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(250 citation statements)
references
References 40 publications
8
227
2
13
Order By: Relevance
“…After this early phase, the increase in PWV tends to disappear and is even reversed as a consequence of the remodelling of the vascular wall. [10][11][12]28 Such experimental findings agree with the slight increase in PWV that we observed in the present study after the 12-week treatment.…”
Section: Commentssupporting
confidence: 93%
See 2 more Smart Citations
“…After this early phase, the increase in PWV tends to disappear and is even reversed as a consequence of the remodelling of the vascular wall. [10][11][12]28 Such experimental findings agree with the slight increase in PWV that we observed in the present study after the 12-week treatment.…”
Section: Commentssupporting
confidence: 93%
“…[8][9][10][11][12]28 Furthermore, in patients with hypercholesterolaemia, radial artery compliance was found to increase to a larger extent after a two-year treatment than after a six-month treatment of simvastatin. 15,29 Finally, all these findings taken together agree with the clinical observations that, although favourable changes in lesion composition were observed within three months of statin treatment, clinical trials suggest that event reduction takes six-twelve months after initiation of treatment.…”
Section: Commentsmentioning
confidence: 92%
See 1 more Smart Citation
“…15 The purpose of the present study was to determine the long-term effects of statins on BP control and PWV in hypertensive hyperlipidaemic patients undergoing antihypertensive therapy. Since recent in vivo studies in rabbits 16 and in vitro data [17][18][19] have indicated that hydrophilic and lipophilic statins have different effects on apoptosis, proliferation of vascular smooth muscle cells, and collagen production by vascular smooth muscle cells, in the present study we evaluated the effects of a hydrophilic drug, pravastatin, and two lipophilic drugs, simvastatin and fluvastatin, on the PWV of hypertensive patients with high serum cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased collagen content translates to less stable atherosclerotic plaques, capable of rupture with associated thrombosis and infarction (Libby & Aikawa, 2002). Increased collagen content and strength of the atherosclerotic plaque may also be part of the benefit afforded by lipid lowering (Aikawa et al, 1998) and statin (Fukumoto et al, 2001) therapies.…”
Section: Role Of Ascorbate In Preventing and Stabilizing Atheroscleromentioning
confidence: 99%